ROLE OF NF-ΚB IN CONNECTIVE TISSUE DEGRADATION IN RAT HEART DURING EXPERIMENTAL METABOLIC SYNDROME - Akimov, O.Ye.; Mykytenko, A.O.; Kostenko, V.O.; Yeroshenko, G.A. (World of Medicine and Biology, 2024)
In recent years more attention has been paid to regulatory functions of connective tissue’s extracellular matrix. The aim of this study is to evaluate influence of NF-κB activation inhibitor on concentration of different fractions of glycosaminoglycans, L-hydroxyproline and sialic acids in rat heart during metabolic syndrome modelling. Research was conducted on 24 male Wistar rats weighing 190–260 g divided into 4 groups: control group; ammonium pyrrolidinedithicarbamate (PDTC) administration group; metabolic syndrome group (MetS group); combined administration of PDTC and MetS modelling group. Administration of PDTC during MetS modelling decreased total glycosaminoglycans, heparin-heparan and keratan-dermatan fraction concentration by 22.53 %, by 21.66 % and by 59.64 %, respectively, but increased chondroitin fraction by 62.1 % compared to MetS group. Concentration of L-hydroxyproline and sialic acids decreased by 26.95 % and by 17.37 %, respectively. Activation of nuclear transcription factor NF-κB in rat heart during metabolic syndrome modelling leads to increased intensity of extracellular matrix degradation.